-8(t-5)-(t+3)=10

Simple and best practice solution for -8(t-5)-(t+3)=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(t-5)-(t+3)=10 equation:


Simplifying
-8(t + -5) + -1(t + 3) = 10

Reorder the terms:
-8(-5 + t) + -1(t + 3) = 10
(-5 * -8 + t * -8) + -1(t + 3) = 10
(40 + -8t) + -1(t + 3) = 10

Reorder the terms:
40 + -8t + -1(3 + t) = 10
40 + -8t + (3 * -1 + t * -1) = 10
40 + -8t + (-3 + -1t) = 10

Reorder the terms:
40 + -3 + -8t + -1t = 10

Combine like terms: 40 + -3 = 37
37 + -8t + -1t = 10

Combine like terms: -8t + -1t = -9t
37 + -9t = 10

Solving
37 + -9t = 10

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-37' to each side of the equation.
37 + -37 + -9t = 10 + -37

Combine like terms: 37 + -37 = 0
0 + -9t = 10 + -37
-9t = 10 + -37

Combine like terms: 10 + -37 = -27
-9t = -27

Divide each side by '-9'.
t = 3

Simplifying
t = 3

See similar equations:

| p+7=7-6p | | X+45+35.8=90 | | 5/8c-8=2 | | 92+78=180 | | Y=300x^2-12 | | -41-5x+7x=19 | | (r-4)(r+1)+(r-4)(r+6)= | | 25x-30=-5 | | -x^2-24+45=0 | | X+16.5=90 | | 1.6(2x-1)=2(.4x+.7) | | 12=8n-(2n-3) | | -2y=-6-7x | | -2x-120+12x=40 | | lgx^3+2lgx^2-14=0 | | 42=1(z-3) | | b^2+13b+31=b-5 | | 0.4(4z+7)+2.8=0.6(4z-4) | | 20x+10y=1420 | | 5a^2+10a=0 | | X+7+3=90 | | 64=-4p | | 2(x+3)(x+3)-5=14x+17 | | (x*11)+(y*9)=360 | | 8j=40 | | x^2-12x+27=2x^2-12x+18 | | 7r^2+36r+5=0 | | 8r^4+32r^2+32=0 | | 16x+1.0625x= | | 2x+6-4(x+1)=5x+6 | | =2c+5 | | (4x+1)(x+1)=0 |

Equations solver categories